2001
DOI: 10.1086/323046
|View full text |Cite
|
Sign up to set email alerts
|

Far‐Infrared Spectroscopy of Normal Galaxies: Physical Conditions in the Interstellar Medium

Abstract: The most important cooling lines of the neutral interstellar medium (ISM) lie in the far-infrared (FIR). We present measurements by the Infrared Space Observatory Long Wavelength Spectrometer of seven lines from neutral and ionized ISM of 60 normal, star-forming galaxies. The galaxy sample spans a range in properties such as morphology, FIR colors (indicating dust temperature), and FIR/Blue ratios (indicating star-formation activity and optical depth).In two-thirds of the galaxies in this sample, the [C II] li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
757
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(836 citation statements)
references
References 65 publications
71
757
8
Order By: Relevance
“…The theoretical model of varying a CO by Wolfire et al (2010), assuming H 2 column density of 10 22 cm −2 in a molecular cloud, agrees well with observational results based on dust-mass at low metallicity (Leroy et al 2011;Sandstrom et al 2013). Adopting a solar metallicity value of 8.66 and heating rate/H atom ( ) G n log 0 = −0.3 (from the L L OI FIR studies of Malhotra et al 2001), the Wolfire et al (2010) model also agrees well with our H 2 rotational emission modeled masses.…”
Section: Molecular Gas Mass Using Our Modelsupporting
confidence: 80%
“…The theoretical model of varying a CO by Wolfire et al (2010), assuming H 2 column density of 10 22 cm −2 in a molecular cloud, agrees well with observational results based on dust-mass at low metallicity (Leroy et al 2011;Sandstrom et al 2013). Adopting a solar metallicity value of 8.66 and heating rate/H atom ( ) G n log 0 = −0.3 (from the L L OI FIR studies of Malhotra et al 2001), the Wolfire et al (2010) model also agrees well with our H 2 rotational emission modeled masses.…”
Section: Molecular Gas Mass Using Our Modelsupporting
confidence: 80%
“…Results were calculated by integrating to A V = 7, and with a cosmic ray flux rate 100 times that of the Milky Way. For reference, the approximate values for Main Sequence galaxies (Malhotra et al 2001), local starbursts (Stacey et al 1991), and local ULIRGs (Davies et al 2003) are shown. The average density for the four DSFGs without a constraint on G 0 is shown at the bottom.…”
Section: Pdr Modelling Resultsmentioning
confidence: 99%
“…Graciá-Carpio et al, 2011) at high-redshift have all been detected in [CII]. The line is thought to be an important coolant in the ISM, and can make up as much as 1% of the far infrared luminosity of a galaxy (Nikola et al, 1998;Malhotra et al, 2001;Stacey et al, 2010). However, the sites of origin of [CII] emission can be diverse, and thus its power as a diagnostic for the physical conditions in the ISM of early Universe galaxies is still debated.…”
Section: Atomic Linesmentioning
confidence: 99%
“…However, present-epoch ULIRGs emit roughly ∼ 10% of the expected [CII] flux, given their far infrared luminosities (e.g. Malhotra et al, 1997Malhotra et al, , 2001Luhman et al, 1998Luhman et al, , 2003. A variety of possible explanations have been posited for the apparent deficit.…”
Section: The [Cii]-fir Deficit In Galaxiesmentioning
confidence: 99%